The role of the French Federation of the National Liberation Front in the supervision of Algerian immigrants in favor of the Algerian revolution through the testimony of Abdelhafid Tayeb HAMMANI, a leader of the Federation in Paris - benazouaou, fateheddine (Journal of Social Sciences and Humanities, 2021)
I relied in this study on the oral testimony of Moudjahid Abdelhafid Tayeb HAMMANI, one of the leaders of the National Liberation Front in Paris, and considering the importance of this type of source in historical studies, I stopped at the beginning of the article on the role of oral testimony in the writing of the history of the Algerian revolution. I showed its importance as an essential source that complements other handwritten and printed sources, and I explained its method and its main foundations so that it would be a valid tool in the documentation process. I then talked about the biography of the author of the testimony and the importance of this one in the writing of the history of the Federation of the National Liberation Front in Paris; I mentioned the intellectual training of Moudjahid Tayeb HAMMANI (in his hometown of Zemmaura) and professional (French Navy in Bejaia), the circumstances of his moving to France and his enlistment in the Federation of the National Liberation Front and the most important command responsibilities that he assumed in the pyramid of the secret organization of the revolution in Paris, and I used these facts to provide objective arguments to justify the legitimacy to rely on his testimony in the documentation process to study the history of the French Federation of the National Liberation Front. Then I gave an overview of the history of this federation since its creation in 1954 to 1962. My main effort in this research was to study the political, military and financial organizational structure of the Federation of the National Liberation Front. I followed its evolution and explained its working mechanism and how it recruited Algerian immigrants in favor of the revolution. Finally, I spoke about the organization of the Federation of the National Liberation Front in French prisons and its role in the supervision of prisoners for the national cause. It should be noted that I relied (along with this oral testimony) on certain documents and also on certain memoirs from senior officials of the French Federation of the National Liberation Front; such as the memoirs of Omar BOUDAOUD, Ali HAROUNE, Salah LOUANCHI and Ahmed DOUME, which I benefited from in the enrichment, comparison and evaluation process, which allowed me to draw important results that I included in the conclusion of this study.